2016
DOI: 10.1177/1933719115620494
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neutrophil-to-Lymphocyte Ratio Combined With CA-125 to Distinguish Endometriomas From Other Benign Ovarian Cysts

Abstract: Although NLR is a simple and easily applicable marker, CA-125 is superior for differentiating endometriomas from other benign ovarian cysts. The combination of these 2 markers improves diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 35 publications
4
48
3
2
Order By: Relevance
“…Kim et al [21] reported that no significant correlation between CA125 and NLR in endometriosis patients, which is consistent with the result of the present study but contrary to the result reported by Cho et al [19] and Tokmak et al [7] Therefore, further studies are needed to evaluate these findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Kim et al [21] reported that no significant correlation between CA125 and NLR in endometriosis patients, which is consistent with the result of the present study but contrary to the result reported by Cho et al [19] and Tokmak et al [7] Therefore, further studies are needed to evaluate these findings.…”
Section: Discussionsupporting
confidence: 85%
“…[16] Numerous studies demonstrated that both PLT and NEU were implicated in the pathogenesis of endometriosis and adenomyosis. [15,17,18] Cho et al [19] and Tokmak et al [7] reported that NLR was significantly positively correlated with the stage of endometriosis, and the combination of NLR and CA125 was more sensitive than CA125 alone for the differential diagnosis of endometriomas, which would be useful in identifying symptomatic patients with early-stage endometriosis. Therefore, we searched the probable relationship of these blood parameters with adenomyosis-derived PDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutrophil‐to‐lymphocyte ratio (NLR) has been proposed as a potential measure of disease severity. The NLR was positively correlated with the severity of endometriosis, and NLR combined with serum carbohydrate antigen (CA)125 level was indicative of disease progression and effective as a diagnostic tool for endometrioma . NLR was also found to be valuable for the diagnosis of endometriosis in patients with CA125‐negative serum .…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) is a simple biomarker for inflammation; in a recent study, NLR was introduced as a marker in various diagnostic and prognostic gynecological procedures [15]. NLR has been also studied in some acute and chronic inflammatory diseases of the central nervous system.…”
Section: Www Journalsviamedicapl/ginekologia_polskamentioning
confidence: 99%